Head size and intelligence: relationships within Homo sapiens species - Henneberg, Maciej; Budnik, Alicja; Pezacka, Małgorzata; Puch, Alicja E. (Anthropological Review, 1984)
In the present paper a hypothesis is advanced stating that in man there is no direct link between intelligence and body size, most specifically head size (brain size), within normal ranges of their variability. Considerable variability of human intelligence, being undoubtedly, though only partly, heritable [Cavalli-Sforza and Bodmer 1971] must be therefore based upon physiological and biochemical variability of brain, but not upon its macrostructural differentiation. In the present work material consists of head dimensions, stature and intelligence measurements taken on 173 first and second year medicine students at the University of Poznań collected by the late Professor Adam Wrzosek in 1930, and measurements of the same variables taken in exactly the same way on 155 male and 151 female first year medicine students of the Silesian Medical School at Katowice by the present authors in 1983. Age of all the students oscillated around 20 years, the majority of them had parents with the university level education (see colum „wyższe” in table 2). Head and body measurements were taken according to standard anthropometric techniques, cranial capacity was calculated from Lee-Pearson formulae given in the text. For the purposes of the present work intelligence was defined as ability for storage and processing of information. Both in case of 1930 Wrzosek’s materials and in our study the same test was used for measurement of intelligence. The test was constructed in 1920-s by S. Baley, Professor of Psychology at the University of Warsaw and especially adapted by him to measuring mental abilites of Polish high school graduates. The test is still valid in light of present-day Polish psychological standards. Its walidity is corroborated in the present paper by observation that among all examined students nobody attained either the maximum nor the minimum score. Distributions of individual scores (table 1, figure 1) are unimodal, slightly skewed, close to a normal distribution. Rage of variablity is large testifying considerable differences in inteligente among individuals despite their uniform formal education, Morphological variables show normal range and mode of variation (table, 3 and 4) only their arithmetic means are higher than average for the whole population — an understandable situation with individuals belonging to upper social strata. Morphological variables, as opposed to intelligence are sensitive for student’s parents educational status, the lowest this status the łowest averages of morphological characters become. The aforesaid is true for both pre- and postwar students. Intragroup interdependences between test scores and values of morphological characters are shown in tables 3 and 4, while table 5 gives a summary of data from literature. A general conclusion to be drawn from these is that relationship between “intelligence” and head size is .at best very weak. The question of relation between body size (stature) and intelligence is still more difficult to answer. It seems that for a configuration of relationships: larger body — bigger brain — higher intelligence, a casual coincidence of these three variables resulting from the operation of the third factor (as eg. generally better care of children in some families creating better opportunites for both mental and physical development) is responsible. The above conclusion seem to find support in the lack of any relationship between cranial capacity, stature and intelligence on intergroup level of comparisons (table 6, see also table 3). Such comparisons are rare because tests of intelligence applied to various groups are different or cultural backgrounds differ preventing a valid comparison. In our case we deal with three groups (małe students of 1930, male students of 1983 and femal students of 1983) of the same cultural background whose intelligence was measured by the same test but who differ in their bodily dimensions. Differences in cranial capacity and stature are very large — of the order of one standard deviation, while there is practically no difference in intelligence test score averages between groups. We are of the opinion that the amount of interdependence between brain (head) size and mental abilities within our species as well-as within the family Hominidae has been largely overstimated. Physiological and biochemical differences between brains as well as the kind (not an amount or quantity) of their contents are probably more important than structural changes. Nevertheless the question of biological basis for differentiation of human intelligence remains open.